2021
DOI: 10.1002/open.202000255
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis‐Inhibitory Effect and Possible Mechanisms of Ellagitannin Geraniin

Abstract: The search for safe and effective ferroptosis‐inhibitors has become an important topic. Geraniin, an ellagitannin bearing hexahydroxydiphenoyl (HHDP) and dehydrohexahydroxydiphenoyl (DHHDP) groups, was observed to inhibit erastin‐induced ferroptosis in bone marrow‐derived mesenchymal stem cells (bmMSCs). To determine the mechanism, geraniin was further analyzed using UV‐vis spectra and several colorimetric assays, where its IC 50 values were always much lower than that of the Trolox posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The reaction of 16-DOXYL-stearic acid • with 4.0 mg/mL chebulagic acid proceeded under the conditions described in a previous method [ 70 ]. Briefly, a methanol solution of the sample was mixed with a methanol/6-DOXYL-stearic acid • solution with a molar ratio of 1:2, and the resulting mixture was incubated for 24 h at room temperature in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…The reaction of 16-DOXYL-stearic acid • with 4.0 mg/mL chebulagic acid proceeded under the conditions described in a previous method [ 70 ]. Briefly, a methanol solution of the sample was mixed with a methanol/6-DOXYL-stearic acid • solution with a molar ratio of 1:2, and the resulting mixture was incubated for 24 h at room temperature in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a large number of studies have shown that PACs activate the Nrf2-HO-1 pathway and ameliorate CIRI, bringing a new direction for CIRI treatment ( Chumboatong et al, 2020 ). In 2022, Yuan et al found downregulation of oxidative stress and neuronal death after injection of the phenolic substance geraniin by the middle cerebral artery occlusion-reperfusion (MCAO/R), and OGD/R models, as well as by neurological scoring assays, CCK8 assessment, TUNEL staining, detection of cells by flow cytometry, and Western blotting assessment ( Chen et al, 2021 ). Meanwhile, they found that the infarcted portion of brain tissue upregulated ex vivo and in vivo Nrf2, HO-1 protein expression in a concentration-dependent manner in the tMCAO model ( Chumboatong et al, 2020 ).…”
Section: Small Molecule Ferroptosis Inhibitorsmentioning
confidence: 99%